`y = tan^(-1) x^2`

To determine the derivative of y, use the formula `(tan ^(-1) u)' = 1/(1+u^2) * u'` .

`y ' = 1/(1+ (x^2)^2) * (x^2)' = 1/(1+x^4) * 2x`

`y ' = (2x)/(1+x^4)`

**Hence, the derivative of `y = tan^(-1) x^2` is `y' = (2x)/(1+x^4)` .**

Posted on

## We’ll help your grades soar

Start your 48-hour free trial and unlock all the summaries, Q&A, and analyses you need to get better grades now.

- 30,000+ book summaries
- 20% study tools discount
- Ad-free content
- PDF downloads
- 300,000+ answers
- 5-star customer support

Already a member? Log in here.

Are you a teacher? Sign up now